A decade of economic reforms in India / the past, the present, the future - Kapila, Raj.; Kapila, Uma. (Delhi : Academic Foundation, 2002)
A collection of well-thought-out lectures delivered by 14 eminant scholars to knowlegeable assemblies, administrative services, and the Reserve Bank of India.
Includes bibliographical references.
aia 19/8/16
Loans
Keywords: India- Economic policy; India